EVALUASI PEMISAHAN PRODUK PERENGKAHAN POLIETILEN MENGGUNAKAN KATALIS AMORPHOUS SILICIA ALUMUNIA DAN HZAM-5 DENGAN ASPEN HYSYS - Sultan Miraj, Muhammad
Plastic is a polymeric material that can be finalized for a wide variety of products, distinguished into several types by their chemical structure. As a raw material that is often used in most industries and other consumers, the use of plastic will eventually become plastic waste. Plastic waste in Indonesia reaches 14% of the total number of daily waste piles or equivalent to 85,000 tons per year. According to the world economic forum (2018), 16% of plastic waste is recycled, but only 2% is effective. This encourages the need and implementation of plastic waste management systems, one of which is through the catalytic cracking process. Given the large amount of plastic waste and the demand for high-quality fuel oil, the polyethylene catalytic cracking process using amorphous silica alumina and HZSM-5 followed by the separation process can be a solution to convert polymer waste (plastic) into high-quality fuel. The study was carried out with an object in the form of a configuration of the separation process of polyethylene cracking products through simulation using aspen hysys to provide optimal separation results. The stage of determining the optimal configuration was carried out using research data published by Sahu et al. The configuration was obtained using a flash separator unit as the optimal configuration that produces the resulting product, namely light and weight oil respectively of 1006.9 kg / hour and 55.4 kg / hour and fuel gas of 79.2 kg / hour. The study continued by evaluating the results of the separation of polyethylene cracking products using the optimal configuration that had been obtained and the research data published by Park et al. The products produced are light oil and weight respectively of 20.2 kg / hour and 1240.4 kg / hour and fuel gas of 37 kg / hour. Then the light and heavy oil products were evaluated and obtained consecutive octane numbers of 79.00 and 101.38.